Genetic Polymorphism of Insulin-Like Growth Factor 1 and Prolactin Receptor Genes in Surti and Mehsana Goats by PCR-RFLP - Ansari, Farheen; Brahmkshtri, Balkrushna; Ramani, Umed; Janmeda, Mamta; Rao, Thakur K (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was planned with the objective to amplify 5’NCR Insulin-like growth factor 1 (IGF1) and 3’UTR Prolactin receptor (PRLR) genes using caprine specific primers by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) in Surti and Mehsana goats. IGF1 gene 5’NCR was found to be monomorphic on restriction digestion with HaeIII, which revealed only one genotype GG in both Surti and Mehsana goats. The allele frequency of G was found to be 1.00 in both the breeds. Restriction digestion of PRLR gene 443 bp fragment with AluI also showed monomorphic pattern. Only one genotype CC was found with an allele frequency of 1.0 in both the Surti and Mehsana goats.